1996
DOI: 10.1002/(sici)1097-4628(19960404)60:1<103::aid-app12>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene during crystallization from the melt as a model for the rheology of molten-filled polymers

Abstract: SYNOPSISPolarized light microscopy shows that polypropylene crystallizes from the melt into a welldistinguished spherulitic structure. Therefore, it provides a useful model for molten-filled polymers, where the growing spherulites are considered to be filler particles dispersed in a matrix fluid. Although spherulites are randomly dispersed in the space, two dispersion models (simple cubic and centered cubic) are discussed to correlate the transformed fraction a ( t ) with the volume fraction of filler q5 (t). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 3 publications
(3 reference statements)
4
26
0
Order By: Relevance
“…2, higher frequencies produce higher moduli and the curves of different frequencies converge at the late stage of crystallization. The same behavior has been observed in the work of Boutahar et al [8] . After an induction period, Gâ€Č(ω) grows more quickly than G″(ω) and then exceeds G″(ω).…”
Section: Evolution Of Dynamic Moduli During Crystallizationsupporting
confidence: 87%
“…2, higher frequencies produce higher moduli and the curves of different frequencies converge at the late stage of crystallization. The same behavior has been observed in the work of Boutahar et al [8] . After an induction period, Gâ€Č(ω) grows more quickly than G″(ω) and then exceeds G″(ω).…”
Section: Evolution Of Dynamic Moduli During Crystallizationsupporting
confidence: 87%
“…One could think of using other approaches by applying more simple models (Boutahar et al 1996(Boutahar et al , 1998Tanner 2002Tanner , 2003van Ruth et al 2006) or empirically based scaling laws between the space filling and the storage modulus (see Coppola et al 2006;Khanna 1993;Pogodina et al 1999). However, it was demonstrated in Steenbakkers and Peters (2008) that such approaches do perform less than the suspension model as used here, and therefore, we will not apply them to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps a network of physical crosslinks is formed (Boutahar et al 1996(Boutahar et al , 1998Coppola et al 2006;Peters et al 2002;Pogodina et al 1999a;Zuidema et al 2001). Subsequently, spherulites grow in this altered melt, the effect of which is well described by suspension-like behavior.…”
Section: Early Stage Of Crystallizationmentioning
confidence: 99%
“…A slight difference in behavior in the two experiments might result in a large error in the hardening function. For instance, Steenbakkers and Peters (2008) found the experiments from Boutahar et al (1996Boutahar et al ( , 1998 showed suspension-like behavior but in order to get quantitative agreement between experiments and simulations, the space filling obtained from DSC measurements had to be adjusted significantly.…”
Section: Introductionmentioning
confidence: 99%